Sorting out the signal: Do multiple measures of teachers’ effectiveness provide consistent information to teachers and principals? - Strunk, Katharine O.; Weinsten, Tracey L.; Makkonen, Reino (Education Policy Analysis Archives, 2014)
There is increasing policy interest in the use of standards-based multiple measure teacher evaluation systems that include both observational and value-added measures of teacher effectiveness. The growing literature that assesses the relationships between these measures does so mainly in academic settings using a validity lens. While valuable in their own right, this evidence from research-based settings provides little evidence about how teachers and principals receive the different signals from multiple measures of effectiveness when implemented in district contexts. Using pairwise correlations and a series of ordinary least squares regressions, this study assesses the relationships between value-added measures of teacher effectiveness and an observational measure of teacher practice as implemented in a district's pilot of a new standards-based multiple-measure teacher evaluation system. We find moderate correlations between value-added and observation-based measures, indicating that teachers will receive similar but not entirely consistent signals from each performance measure. We conclude by highlighting considerations for districts working to develop and implement standards-based multiple-measure teacher evaluation systems.